STEM-Integrated Student Worksheets on Space Figure Using the Discovery Learning Model for Elementary School Students - Deka Silvi Astryani; Agus Susanta; Irwan Koto; Edi Susanto (Profesi Pendidikan Dasar, 2022)
This study aimed to create student worksheets using the STEM approach for fifth-grade students of Bengkulu State Elementary School. The research used the ADDIE model and had two classes of 22 students as its sample population. The research tools were validation sheets, student assessment sheets, and learning outcome test sheets. Data was collected through multiple methods and analyzed using expert validation and reliability tests. The results showed that the STEM-based worksheets were highly feasible in terms of material, language, and presentation, and effective in improving student learning outcomes.